2007
DOI: 10.1523/jneurosci.1106-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

SK Channels Provide a Novel Mechanism for the Control of Frequency Tuning in Electrosensory Neurons

Abstract: One important characteristic of sensory input is frequency, with sensory neurons often tuned to narrow stimulus frequency ranges. Although vital for many neural computations, the cellular basis of such frequency tuning remains mostly unknown. In the electrosensory system of Apteronotus leptorhynchus, the primary processing of important environmental and communication signals occurs in pyramidal neurons of the electrosensory lateral line lobe. Spike trains transmitted by these cells can encode low-frequency pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
149
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(171 citation statements)
references
References 73 publications
20
149
2
Order By: Relevance
“…Moreover, recent studies have shown that these mechanisms not only alter the spike count variance but also can alter its mean and possibly higher moments ). Moreover, these mechanisms can also strongly alter temporal frequency tuning (Ellis et al 2007;Mehaffey et al 2008;Lindner et al 2009;Peron and Gabbiani 2009). Yet, to date, all studies that have explored the role of nonrenewal spike train statistics on information transmission or signal detection have done so by comparing models that display identical first-order ISI statistics and frequency tuning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, recent studies have shown that these mechanisms not only alter the spike count variance but also can alter its mean and possibly higher moments ). Moreover, these mechanisms can also strongly alter temporal frequency tuning (Ellis et al 2007;Mehaffey et al 2008;Lindner et al 2009;Peron and Gabbiani 2009). Yet, to date, all studies that have explored the role of nonrenewal spike train statistics on information transmission or signal detection have done so by comparing models that display identical first-order ISI statistics and frequency tuning.…”
Section: Discussionmentioning
confidence: 99%
“…1b) does not capture this. However, a plot of the current ISI as a function of the preceding one, also known as the ISI return map (Doiron et al 2003;Ellis et al 2007;Toporikova and Chacron 2009) (Fig. 1c), can be used to illustrate this fact.…”
Section: Negative Interspike Interval Correlations At Lagmentioning
confidence: 99%
“…SK channels can regulate numerous aspects of neuronal dynamics including: spike frequency adaptation (Pedarzani et al, 2005), dendrosomatic coupling (Cai et al, 2004), as well as synaptic integration and potentiation (Faber et al, 2005;Ngo-Anh et al, 2005). The links between SK channel kinetics and behaviourally relevant neuronal computations have only recently begun to be examined for the SK2 subtype (Ellis et al, 2007b). In the following, we highlight some recent results on the role played by these channels in determining pyramidal cell dynamics and frequency tuning.…”
Section: Sk2 Channels Contribute To Tuning Differences Observed Acrosmentioning
confidence: 99%
“…The dendritic origin of the DAP can be revealed by blocking dendritic sodium channels with the application of TTX to the apical dendrites, eliminating the dendritic spike (Fernandez et al, 2005b;Mehaffey et al, 2005Mehaffey et al, , 2006Turner et al, 1994). This burst mechanism has been shown to be controlled by a variety of intrinsic membrane conductances including persistent sodium currents and high-threshold potassium channels (Ellis et al, 2007b;Fernandez et al, 2005a;Mehaffey et al, 2006;Noonan et al, 2003;Rashid et al, 2001a,b). As channel densities have been shown to vary across the different tuberous maps (Deng et al, 2005;Smith et al, 2006), they may contribute to map-specific computations including frequency selectivity (Metzner and Juranek, 1997;Shumway, 1989a).…”
Section: Regulation Of Pyramidal Cell Burstingmentioning
confidence: 99%
See 1 more Smart Citation